1996
DOI: 10.1016/0735-1097(95)00452-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ligation of patent ductus arteriosus on left ventricular performance and its determinants in premature neonates

Abstract: Ventricular performance is higher in premature infants with than in those without patent ductus arteriosus because afterload is lower in the former group. Although ductal ligation increases blood pressure and systemic resistance, wall stress and ventricular performance are maintained. Our results suggest that the premature newborn maintains ventricular performance during stress, at least in part, by manipulating afterload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…In the same way, we found a high incidence of absent or reverse diastolic¯ow in the subdiaphragmatic aorta which is known to indicate large left-to-right shunting through the PDA [5,6,17,34]. These observations con®rmed previous reports of increased blood pressure after ductal ligation [11] and argue for a possible negative eect of large left-to-right shunting through a PDA.…”
Section: Discussionsupporting
confidence: 86%
“…In the same way, we found a high incidence of absent or reverse diastolic¯ow in the subdiaphragmatic aorta which is known to indicate large left-to-right shunting through the PDA [5,6,17,34]. These observations con®rmed previous reports of increased blood pressure after ductal ligation [11] and argue for a possible negative eect of large left-to-right shunting through a PDA.…”
Section: Discussionsupporting
confidence: 86%
“…In an echocardiogram-based study evaluating pre-and post-PDA ligation cardiac function, it has been demonstrated that left ventricular end-diastolic volume, stoke volume, ejection fraction, and cardiac output were significantly higher before ductal ligation in full-term infants [12]. Using different echocardiographic parameters, such as end-systolic wall stress and contractility, other studies have shown that despite increased afterload with PDA ligation, premature newborn ventricular performance is maintained [13]. Our study appears to validate this observation, inasmuch as all our measured parameters and calculated indices do not demonstrate a statistically significant difference between the neonates that developed hemodynamic decompensation and those who did not.…”
Section: Discussionmentioning
confidence: 95%
“…The presumed cause of early postoperative hemodynamic instability or deterioration after PDA closure is cardiac decompensation or myocardial dysfunction, secondary to acute changes related to occlusion of the ductus [11,12]. Multiple ventricular performance measures have been studied in various animal models, along with human preterm infants, resulting in conflicting conclusions about the cardiovascular ramifications of PDA ligation [11,13,14]. A possible decrement in ventricular performance is thought to occur as a result of an acutely increased systemic vascular resistance and afterload, and an acutely decreased preload after ductal closure [11].…”
mentioning
confidence: 99%
“…The decision to perform the study echocardiogram at this time point was based on several considerations. Prior studies have shown that echocardiograms performed either prior to, or 60 minutes after the surgery, are not associated with the development of post-ligation hypotension (5, 10, 12). On the other hand, echocardiographic measurements made at 6–8 hours after the operation (6) (when infants have already started to develop hypotension) have a strong relationship to the presence of postoperative hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…Although measurements of myocardial performance, made shortly (1–2 hours) after ligation, have not been found to have a strong association with the development of post-ligation hypotension (5, 10, 12), indices of impaired myocardial performance, at 6–8 hours after the operation (closer to the time of clinical deterioration), appear to have a much stronger relationship (6). Prophylactic treatment with milrinone, starting shortly after ligation, has been reported to reduce the incidence of cardiorespiratory instability; however, despite early milrinone treatment, some infants continue to develop post-ligation catecholamine-resistant hypotension (8, 9).…”
Section: Introductionmentioning
confidence: 95%